Toward a Biography of Samora Machel: The Making of a Revolutionary, 1933–1970 ca. Issue 1 (2nd January 2020) - Isaacman, Allen
ABSTRACT: Scholars have written extensively about the role Samora Machel played in FRELIMO during the armed struggle and as the first president of Mozambique. In sharp contrast, we know precious little about Samora's formative years (1963–1970) and how they shaped his political thinking and action. In what ways did his experiences as a herd boy in southern Mozambique, his difficulties in the colonial educational system, his conflictual relationship with the Catholic Church and his work as a nurse and his relations with progressive whites help to radicalise him to shape his commitment to building a non-racial society in Mozambique? To answer these questions this article delves into a substantial body of little-used primary material housed in the Centro de Documentaçāo Samora Machel in Maputo. It also rests on the author's interviews with the Mozambican President, his closest family members, and political confidantes, as well as guerrillas, peasants, and urban workers who had infrequent contact with him.